Baseline cerebrospinal fluid biomarkers of amyloidosis, phosphorylated tau, and total tau relate to greater longitudinal atrophy in regions susceptible to Alzheimer's disease‐related neurodegeneration: Biomarkers (non‐neuroimaging)/Prognostic utility. (7th December 2020) - Moore, Elizabeth E.; Khan, Omair A.; Liu, Dandan; Pechman, Kimberly R.; Acosta, Lealani Mae Y.; Bell, Susan P.; Landman, Bennett A.; Blennow, Kaj; Zetterberg, Henrik; Hohman, Timothy J.; Gifford, Katherine A.; Jefferson, Angela L.
Abstract: Background: Cerebral atrophy patterns can distinguish normal cognition from Alzheimer's disease (AD), but neuropathological drivers of these patterns are still not well understood. This study examined baseline cerebrospinal fluid (CSF) biomarkers of AD pathology (amyloid‐beta (Aβ), phosphorylated tau (p‐tau)); neurodegeneration (total tau (t‐tau)); synaptic dysfunction (neurogranin); and neuroaxonal injury (neurofilament light (NFL)) in relation to longitudinal atrophy patterns for two common AD neuroimaging signatures. Method: Vanderbilt Memory and Aging Project participants free of clinical dementia or stroke (n=153, 72±6 years) underwent baseline fasting lumbar puncture for CSF collection and serial T1 ‐weighted neuroimaging at 3T (baseline, 18‐months, 3‐years, 5‐years). Images were post‐processed using FreeSurfer. AD imaging signatures were calculated using published guidelines (McEvoy et al., 2009; Schwarz et al., 2016). Linear mixed effects models related each baseline CSF biomarker to each AD signature trajectory using biomarker x follow‐up time interactions, adjusting for age, sex, race/ethnicity, education, diagnosis, apolipoprotein ( APOE )‐ε4 status, and follow‐up time. Secondary models tested CSF biomarker x APOE‐ε4 interactions on longitudinal AD signature trajectory. Result: Mean follow‐up time was 3.4±1.1 years. Lower baseline CSF Aβ (p<0.001), higher t‐tau (p=0.04), and higher p‐tau levels (p=0.01) were associated with a faster rate of cortical thinning in the McEvoy AD signature. Baseline CSF biomarkers were unrelated to Schwarz AD signature trajectory (p‐values>0.16). APOE‐ε 4 interacted with baseline CSF p‐tau, t‐tau, neurogranin, and NFL on both AD signatures (p‐values<0.04). APOE ‐ε4 also interacted with CSF Aβ on the Schwarz AD signature (p=0.008). Associations linking baseline CSF Aβ, p‐tau, t‐tau, and neurogranin with faster atrophy patterns were driven by APOE ‐ε4 carriers (p‐values<0.05). Conclusion: Increased baseline evidence of cerebral amyloidosis, phosphorylated tau, and neurodegeneration related to faster rates of cortical thinning in AD‐affected regions over a mean 3.4 year follow‐up period. Associations linking amyloidosis, phosphorylated tau, neurodegeneration, and synaptic dysfunction to cortical thinning are driven by APOE ‐ε4 carriers, suggesting grey matter regions susceptible to the longitudinal neurodegenerative effects of AD pathology may be even more susceptible in APOE ‐ε4 carriers, perhaps due to the effects of APOE ‐ε4 on blood‐brain barrier compromise, vascular dysregulation, or inflammatory activation.